Directions of the study of commendable linguistic units in the Kazakh language (Eurasian Journal of Philology Science and Education, 2021)
In the article, the object of linguistic research is commendable and rewarding linguistic units, theirpragmatic and functional aspects are generally considered. Semantic branching of evaluative linguisticunits is the main topic of this article. The author points out that the meaning of commendable linguisticunits in any language is best revealed in communicative communication. Depending on the scope oftheir application, it is necessary to highlight the stylistic specifics, the grammatical design of these unitsin relation to the individual characteristics of the personality, their orientation relative to the respondent,anthropo-relevance that forms the personality of a person. The article also examines the pragmatism ofthese units in terms of the implementation of the final strategy and other areas of research, which accordinglydetermines the relevance of the topic.Commendation linguistic units are an integral part of the entire category of linguistic assessmentunits. They have a socially oriented feature, acquire a social and communicative meaning. The socialnature of these units contributes and helps to define their pragmatics in accordance with the contextwithin the text. If the main meaning of these units arises from polite use, under other circumstances, themeanings of irony, ridicule, and humiliation can also be revealed.Depending on the semantic meaning, the following types of commendable linguistic units can bedistinguished: 1) positive or negative meaning; 2) depending on the grammatical meaning – transmittedthrough adjectives, numbers, adverbs, adverbs, verbs, conjunctions; 3) relatively pragmatic meaning –used in direct and figurative meaning; in terms of stylistic separation, they are used in all kinds of styles. The article also points out the need to summarize commendable linguistic units and compile aseparate dictionary.